Handa't may pasya a proposed website manual on the process of implementing an adolescent reproductive health campaign for Palawan communities - Salen, Abigail B.
The reproductive health crisis remains one of the most pervasive issues endured globally and locally--with thousands of young men and women disadvantaged due to incomprehensive sex education curricula, lack of access to contraceptives, high rates on unintended pregnancies, and lack of HIV and STI post-care treatment (Morris and Rushwan 540). This condition is similarly occurring in the province of Palawan, Philippines with 1916 registered adolescent-aged live births in 2020 alone (Philippine Statistics Authority MIMAROPA 3). Palawan has also been reported to have the highest rates of HIV and STI transmissions in the region of MIMAROPA--taking up 47.8% out of the total of 805 cases in the year 2019 (Magdayao). Such context has inspired a study that aims to hep an already established Palawan-based NGO, Roots of Health, in expanding their reach and making their reproductive health efforts for adolescents more accessible and impactful.